Distribution of Virulence genes in Streptococcus pneumoniae Isolated from Different Baghdad Hospitals - Dina Muthana Fahran; Basima Qasim Hasan Al-Saadi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Streptococcus pneumoniae causes serious infections (pneumonia, meningitis and bacteremia) withsignificant morbidity and mortality rates. The goal of this study is to isolate and identify S. pneumoniaefrom clinical samples in Baghdad City hospitals in order to explore the presence of three virulencegenes (lytA, ply and psaA) in clinical isolates. A total of 120 separate clinical samples were obtainedfrom inpatients and outpatients with upper and lower respiratory tract infections at different hospitals inBaghdad. Twenty-five isolates of S. pneumoniae were identified by using cultural, morphological andbiochemical characteristics as well as the diagnosis by VITEK2 system. Clinical samples were includingsputum 19 isolates (76%) and urine 6 isolates (24%). The results of collected specimens showed thatmale’s percentage is highest than female’s patients, which was out of 25 isolates are 15 (60%) malesand 10 (40%) females, The results also showed that it is much more common in elderly people thanin younger people. The genomic DNA of bacterial isolates was applied in a polymerase chain reaction(PCR) to amplify certain genes. The PCR results were: Six isolates (24%) show positive results forthe presence of lytA gene. Five isolates (20%) showed positive results for the presence of ply gene.Twenty-three isolates (92%) show positive results for the presence of psaA gene. As concluded fromthe present study, that the results exhibited that the presence of the virulence genes can be consideredas a serious issue.